A Review on Association Rule Mining with Regression Techniques for Effective Data Mining - Dr. C. Nalini, Srinu Dharavath, Dr. D. Natarajasivan (International Journal of Control and Automation, 2020)
A Wal-Mart salesman was trying to surge the sales data of the store by combining the commodities together and putting discounts on those products. The goods are clearly distinct thus he found that nurturing kids is exhausting. Data Mining, also known as KDD [1], to find irregularities, associations, arrangements, and tendencies to forecast consequences. Apriori algorithm is a standard process in data mining. It is utilized for mining recurrent sets of items and related association rubrics. It is formulated to work on a database comprising of a lot of transactions. It is very vital for operative Market Basket Investigation and this assistance the patrons in buying their substances with more effortlessness which escalates the sales of the markets. While finding goods to be associated together, it is imperative to have some association on which the commodities can be listed together. In this research work a hybrid method has been proposed to minimize association rules using optimization algorithm Differential Evolution with Apriori Algorithm.